Changing South-Pacific Identities and Transformations - Tcherkezoff, Serge (ANU Press, 2008)
The texts collected in this volume take an anthropological approach to the variety of contemporary societal problems which confront the peoples of the contemporary South Pacific: religious revival, the sociology of relations between local groups, regions and nation-States, the problem of culture areas, the place of democracy in the transition of States founded on sacred chiefdoms, the role of ceremonial exchanges in a market economy, and so forth. Each chapter presents a society seen from a specific point of view, but always with reference to the issue of collective identity and its confrontation with history and change. The collection thus invites the reader to understand how the inhabitants of these societies seek to affirm both an individual identity and a sense of belonging to the contemporary world. In doing so, it informs the reader about the contemporary realities experienced by the inhabitants of the South Pacific, with a view to contributing to an intercultural dialogue between the reader and these inhabitants.